2022
DOI: 10.32014/2518-1491.127
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Distribution of Elements, Environmental Effects, and Economic Potential of Technogenic Waste Materials of Pavlodar Aluminum Plant (Pavlodar, Kazakhstan)

Abstract: doctor of chemistry, professor, academician of NAS RK, president of NAS RK, general director of JSC "Institute of fuel, catalysis and electrochemistry named after D.V. Sokolsky (Almaty, Kazakhstan) H = 4 Editorial board: ADEKENOV Sergazy Mynzhasarovich (deputy editor-in-chief) doctor of chemical sciences, professor, academician of NAS RK, director of the international Scientific and production holding «Phytochemistry» (Karaganda, Kazakhstan) H = 11 AGABEKOV Vladimir Enokovich (deputy editor-in-chief), doctor o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Namely, in the literature [141][142][143][144][145], it has been shown that the number of such stages can be different for different systems. Moreover, in other studies [143][144][145]162,163], it was shown that the staged nature of phase transitions can also be associated with fundamentally different processes. For example, for systems such as those studied in one study [144], it is determined by the formation of hydrophobic-hydrophilic associates (HHA), and for those studied in [145], it is determined by the formation of hydrophilic interpolymer associates (HIA).…”
Section: Methodsmentioning
confidence: 97%
“…Namely, in the literature [141][142][143][144][145], it has been shown that the number of such stages can be different for different systems. Moreover, in other studies [143][144][145]162,163], it was shown that the staged nature of phase transitions can also be associated with fundamentally different processes. For example, for systems such as those studied in one study [144], it is determined by the formation of hydrophobic-hydrophilic associates (HHA), and for those studied in [145], it is determined by the formation of hydrophilic interpolymer associates (HIA).…”
Section: Methodsmentioning
confidence: 97%
“…Along with the positive economic effects, this territory affects the residential area of the city of Pavlodar and should be regularly monitored and studied in order to assess environmental risks and plan measures for the remediation and reduction of contamination in order to preserve the well-being of residents. Recent statistics show a significant increase in respiratory diseases and cancer cases in the Pavlodar region [62][63][64].…”
Section: Introductionmentioning
confidence: 99%